Gauging Uniqueness: Assessment in Special Collections - Barsaga, Agnes; Vallente, Robert; Vinzon, Minette (The 8th International Conference on Emerging Global Trends in University Library Development (ICEGTULD 2019), 2019)
This paper examines the Special Collections (SC) book holdings of De La Salle University Libraries, which aims the following: 1) to profile the book holdings of the SC; 2) to identify the strength and weakness of the collection; 3) to examine the utilization of the collection, and; 4) to determine the uniqueness and rarity of the book collection by comparing the SC book titles to the online catalog of University of the Philippines. The results of this study will provide statistical data that may be used in crafting guidelines for acquisitions, weeding and budget allocations for special collections. This study uses collection assessment through collection-centered techniques by counting the holdings of the SC book collections. Google curling was used to gauge the uniqueness of the book collection.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; collection assessment; special collections; collection analysis; counting holdings